Development and usability evaluation of an online self‐management intervention for fear of cancer recurrence (iConquerFear). Issue 1 (10th September 2019) - Smith, Allan "Ben"; Bamgboje‐Ayodele, Adeola; Butow, Phyllis; Klein, Britt; Turner, Jane; Sharpe, Louise; Fardell, Joanna; Beatty, Lisa; Pearce, Alison; Thewes, Belinda; Beith, Jane; ,; et al.
Abstract: Objective: To develop and evaluate the usability of iConquerFear, an online self‐management adaptation of an efficacious face‐to‐face therapist‐delivered treatment for fear of cancer recurrence (FCR). Methods: iConquerFear development was theory based and person based. Development was guided by Ritterband et al's behaviour change model for internet interventions. iConquerFear end users (cancer survivors) provided iterative feedback in accordance with Yardley et al's person‐based approach to maximise engagement and usability. Online focus groups and cognitive interviews were conducted to evaluate the usability of iConquerFear. Discussions were recorded, transcribed verbatim, and thematically analysed. Results: Five online FCR modules were developed. Twenty‐three cancer survivors (47% of those eligible) participated; 11/23 (58%) were breast cancer survivors, and average age was 53 years (SD = 10.8). Thematic saturation was reached after six focus groups (n = 16) and seven individual think‐aloud interviews. Thematic analysis produced five overarching themes: easy navigation essential; satisfaction and engagement with content; flexible access is key; normalising and empowering; and a useful first step. Conclusions: Online self‐management interventions like iConquerFear have the potential to address the unmet supportive care needs reported by burgeoning numbers of cancer survivors. However, that potential may not be realised unless interventions are rigorously developed and user tested, as benefits are constrained by limited engagement. Themes from the usability testing of iConquerFear highlight the importance of developing flexible, tailored, interactive, and contextual online self‐management interventions for people with cancer.